Inflammation and prostate carcinogenesis. (31st July 2012) - Nakai, Yasutomo; Nonomura, Norio
Abstract Quite a few epidemiological studies including meta‐analyses indicate that prostate inflammation is associated with increased risk of prostate cancer. The cause of inflammation in the prostate is speculated to be several microorganisms that cause prostatitis or sexually transmitted infections. Other specific microorganisms, such as xenotropic murine leukemia virus‐related virus, are also reported to relate to the development of prostate cancer; however, the contribution of this microorganism to prostate cancer development needs to be carefully interpreted. Environmental factors, especially dietary factors, might also be associated with prostate cancer development. Among related dietary factors, charred meat carcinogen 2‐amino‐1‐methyl‐6‐phenylimidazo[4, 5‐b]pyridine might be a link between environmental factors and inflammation, because 2‐amino‐1‐methyl‐6‐phenylimidazo[4, 5‐b]pyridine has the potential to accelerate prostate inflammation through its estrogenic effect. In light of these findings, preventing or reducing prostate inflammation might be one strategy for chemoprevention of prostate cancer.